Socialization and Training on Ecoenzyme Manufacture in the Enviromoms Community, in Bojong Depok Baru II Housing, Sukahati, Cibinong, Bogor District - Nuraeni, Farida; Iryani, Ani (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2023)
ABSTRACT Enviromoms is a community created to improve virtual community-based community empowerment programs into solutions to overcome waste problems. One strategic role that has the potential to reduce the amount of waste generated by housewives. The aim of this program is to form a virtual community of Enviromoms housewives that focuses on the environmental sector, educate Enviromoms members and the community regarding zero waste homes, and form a waste-free Rukun tetangga pilot area. This program was attended by 20 mothers. Solution offered by the university, in this case the Chemistry Study Program, Faculty of Mathematics and Natural Sciences, Pakuan University, is to provide counseling about making ecoenzymes. The lack of knowledge of the community, especially the Enviromoms community group, in processing and optimizing the potential of organic waste from the kitchen needs to be improved through outreach and training. The output targets of proposal grant to be achieved include publication in the JPMI journal at Pakuan University, publication in the Jabar Online mass media, videos of the implementation of service activities which can be accessed online and improving skills in making ecoenzymes for mothers who are members of the Enviromoms community. The planned activities that will be carried out include socialization about ecoenzymes and their benefits, and training in making ecoenzymes from organic waste in the kitchen and practice by the participants.